Development of repetitive current control for lead acid battery using arduino - Abdul Mutahar, Lidyanur (2014)
This project focused on development of repetitive current control for lead acid battery using Arduino. The project uses Buck-Boost converter circuit with reference voltage of 14V from lead acid battery. The range of buck operation input voltage is between 18V to 15V while boost operation input voltage range is between 10V to 13V. The current sensor uses in this project is to measure the output current with rating 50 A versions and 40 mV/A output sensitivity. The results of simulation output current slightly increase with the minimum value of 0.11A and the maximum value of 0.26A. While the hardware output current is constant at1.71A for 10V to 18V. This project uses MATLAB R2013b and Arduino UNO microcontroller with specification of ATmega328 processor. A repetitive current controller is been developed using MATLAB Simulink Toolbox which communicates with Arduino Support Package library in order to generate the pulse width modulation (PWM) signals.The project with the aid of MATLAB software and Arduino is able to develop repetitive current control for lead acid battery